A BUDDHIST VIEW OF HAPPINESS. Issue 1 (19th February 2014) - Ricard, Matthieu
Abstract In Buddhism, happiness is achieved when a person can perceive the true nature of reality, unmodified by the mental constructs we superimpose upon it. This authentic happiness comes from having an exceptionally healthy state of mind that underlies and suffuses all emotional states and that embraces all the joys and sorrows that come one's way. The mental states necessary for authentic happiness are not simply found or happened upon. Rather, happiness is achieved through mental training that purges the mind of afflictive emotions, such as hatred and compulsive desire, which literally poison the mind, and above all through the eradication of ignorance. This article discusses the Buddhist conception of happiness and its attainment. In particular, the article addresses the methods and practices that Buddhism employs to train the mind to achieve authentic happiness and the recent developments in contemplative neuroscience that complement and advance these methods.